A Feminist Call to Be Radical: Linking Women's Health and Planetary Health. Issue 3 (September 2020) - Tanyag, Maria
Abstract : iwishi couldw riteth epoemi wantor eadina timeo fcrisis {repeat} ineed towriteth epoemi wantor eadina timeo fcrisis {repeat} thisi snotth epoemi needtow riteina timeo fcrisis {repeat} thisi sjustat est ofawri terina timeo fcrisis {repeat} —Teresia Teaiwa (2013) Reflecting on the two previous conversations in Politics & Gender (2015 and 2017) regarding the diverging paths in global political economy and security studies that feminist international relations (IR) scholars have taken, I am reminded of Teresia Teaiwa's poetry, which for me speaks about how crisis gives birth to the radical starting points of our feminist inquiries. We are all undoubtedly on the cusp of ever-intensifying forms of insecurities, and peoples who have least contributed to their creation and hastening are bearing the worst impacts. It is projected that by 2100, the compounded threats that humanity will face as a result of climate change will be in multitudes across five main human systems: health, water, food, economy, infrastructure, and security (Cramer et al. 2018; Mora et al. 2018, 106). The complex consequences of climate change demand an approach that encompasses the interaction effects of different risks and hazards. However, across natural and social sciences so far, the norm has been to focus on specific aspects of human life and to examine hazards–including conflict and violence—in isolation from one another. We then run the risk of misleading ourselves with partial, if not incorrect, assessments of the global processes surrounding climate change. In particular, we are yet to understand the multiscalar dynamics of environmental degradation and extreme weather as they are entangled with other crises such as armed conflicts, health pandemics, economic recessions, and resurgences of authoritarian leadership. Whether feminist or not, we simply cannot afford to think in "camps" instead of "bridges" given the nature of the multiple crises we as humanity are facing. As Anna M. Aganthangelou (2017, 741) points out, "[g]lobal politics are never just 'economic' or 'security' issues, " so the kind of assumptions we hold and how these inform the questions we raise need to "attend to the highest stake of politics: existence."